Teknologi Sebagai Media Konstekstualisasi Nyanyian Gerejawi Bagi Remaja - Maringka, Frangki Rafli; Tarumingi, Denny Adri (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2024)
This research discusses Technology as a contextual medium in maintaining ecclesiastical singing for adolescents in the GMIM Nazareth Wongkai congregation in the Pinaesaan Region. This study explains how the combination of technology in the form of PowerPoint applications in laptops, LCD projectors and sound systems in presenting liturgy, lyrics and accompaniment of ecclesiastical singing music in work and time at the same time, so that this can be contextualized with adolescents who tend to be more interested in the method of worship. Then in this study using a qualitative research method, which is able to examine the results of research in the field and examine several things that are summarized in the existing problems. The results obtained in this paper are to make it easier for teenagers in the GMIM Nazareth Wongkai congregation to recognize and maintain the use of ecclesiastical singing in every youth worship that is carried out. So that with this combination of technology, teenagers can sing every ecclesiastical song more creatively in every worship, and are able to maintain church traditions, including ecclesiastical songs.